2008
DOI: 10.1007/s11920-008-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Medically serious adverse effects of newer antidepressants

Abstract: Although safer than tricyclic antidepressants and monoamine oxidase inhibitors, the newer antidepressants may be associated with certain medically serious adverse effects, of which cardiovascular adverse effects, seizures, abnormal bleeding, hyponatremia, and agranulocytosis are discussed in this review. Data regarding the incidence and risk factors are summarized, and strategies for reducing the risk of these adverse effects and managing them are suggested. Identification of risk factors, appropriate antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 68 publications
0
23
0
7
Order By: Relevance
“…For instance, the risk of gastrointestinal bleeding was 3.6 times higher in patients taking SSRIs compared to those who do not use these medications. This effect was increased to 12.2 times the risk in the general population for patients who take SSRIs and NSAIDs simultaneously [10]. Barbui et al in a case-control study also found a modestly increased risk of gastrointestinal (GI) bleeding with usage of SSRIs, but no increased risk with tricyclic antidepressants.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, the risk of gastrointestinal bleeding was 3.6 times higher in patients taking SSRIs compared to those who do not use these medications. This effect was increased to 12.2 times the risk in the general population for patients who take SSRIs and NSAIDs simultaneously [10]. Barbui et al in a case-control study also found a modestly increased risk of gastrointestinal (GI) bleeding with usage of SSRIs, but no increased risk with tricyclic antidepressants.…”
Section: Discussionmentioning
confidence: 96%
“…McCloskey et al [6] demonstrated alterations of the platelet function assay in patients taking SSRIs compared to those on a non-serotonergic antidepressant. Mago et al [10] suggested that PFA should be evaluated before elective surgery in patients taking SSRIs. although no data were offered to define the benefits of this test in the presurgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the use of SSRIs and SNRIs has increased because of higher safety profile [35,36], although cardiovascular adverse effects, abnormal bleeding, hyponatremia, seizures, and agranulocytosis should be kept in mind while treating cancer patients [37]. Psychostimulants (e.g., methylphenidate, pemoline, d-amphetamine)are useful in the treatment of depression in cancer, in terminally ill patients, because of their rapid onset of action and effect concentration and attention problems and also on fatigue [38].…”
Section: Balaji Et Almentioning
confidence: 99%
“…Os antidepressivos (ADs) têm sido associados com diversos efeitos colaterais, que se observam mesmo com os ADs mais recentes, ainda que sejam mais seguros que os mais antigos antidepressivos tricíclicos (ADTs) e inibidores da monoaminoxidase (IMAO) 1 . Entre os efeitos colaterais mais comuns e potencialmente graves está a hiponatremia, efeito que tem sido associado, principalmente, a doentes idosos e polimedicados (ou seja: diuréticos, antidiabéticos, anti--inflamatórios não esteroides) 1,2 .…”
Section: Introductionunclassified
“…Entre os efeitos colaterais mais comuns e potencialmente graves está a hiponatremia, efeito que tem sido associado, principalmente, a doentes idosos e polimedicados (ou seja: diuréticos, antidiabéticos, anti--inflamatórios não esteroides) 1,2 . A relação provável entre os ADs e a hiponatremia foi descrita pela primeira vez em 1974 com a amitriptilina e tem sido cada vez mais debatida desde a introdução dos inibidores seletivos da recaptação de serotonina (ISRS) 3 .…”
Section: Introductionunclassified